Effect of Phorate on the Development of Hyperglycaemia in Mouse and Resistance Genes in Intestinal Microbiota - Tingting Cao; Yajie Guo; Dan Wang; Zhiyang Liu; Suli Huang; Changfeng Peng; Shaolin Wang; Yang Wang; Qi Lu; Fan Xiao; Zhaoyi Liang; Sijia Zheng; et al. (MDPI AG, 2022)
Phorate is a systemic, broad-spectrum organophosphorus insecticide. Although it is commonly used worldwide, phorate, like other pesticides, not only causes environmental pollution but also poses serious threats to human and animal health. Herein, we measured the blood glucose concentrations of high-fat-diet-fed mice exposed to various concentrations of phorate (0, 0.005, 0.05, or 0.5 mg/kg); we also assessed the blood glucose concentrations of high-fat-diet-fed mice exposed to phorate; we also assessed the distribution characteristics of the resistance genes in the intestinal microbiota of these mice. We found that 0.005 and 0.5 mg/kg of phorate induced obvious hyperglycaemia in the high-fat-diet-fed mice. Exposure to phorate markedly reduced the abundance of Akkermansia muciniphila in the mouse intestine. The resistance genes vanRG, tetW/N/W, acrD, and evgS were significantly upregulated in the test group compared with the control group. Efflux pumping was the primary mechanism of drug resistance in the Firmicutes, Proteobacteria, Bacteroidetes, Verrucomicrobia, Synergistetes, Spirochaetes, and Actinobacteria found in the mouse intestine. Our findings indicate that changes in the abundance of the intestinal microbiota are closely related to the presence of antibiotic-resistant bacteria in the intestinal tract and the metabolic health of the host.